2015
DOI: 10.1089/ten.tea.2014.0335
|View full text |Cite
|
Sign up to set email alerts
|

A Chitosan-Hyaluronan-Based Hydrogel-Hydrocolloid SupportsIn VitroCulture and Differentiation of Human Mesenchymal Stem/Stromal Cells

Abstract: Three-dimensional (3D) cell culture platforms are increasingly utilized due to their ability to more closely mimic the in vivo microenvironment compared to traditional two-dimensional methods. Limitations of currently available 3D materials include lack of cell attachment, long polymerization times, and inclusion of undefined xenobiotics, and cytotoxic cross-linkers. Evaluated here is a unique hydrogel comprised of polyelectrolytic complex (PEC) fibers formed by hyaluronic acid and chitosan (CT). When hydrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 37 publications
4
28
0
Order By: Relevance
“…Cell numbers then plateaued and were maintained until day 14 of culture. This indicated a balance between apoptotic cell death and proliferation similar as found in culture of human MSCs in a chitosanhyaluronan-based hydrogel in vitro [22]. The cell density at plateau phase was approximately 20%-30% of loaded cells.…”
Section: Discussionsupporting
confidence: 70%
“…Cell numbers then plateaued and were maintained until day 14 of culture. This indicated a balance between apoptotic cell death and proliferation similar as found in culture of human MSCs in a chitosanhyaluronan-based hydrogel in vitro [22]. The cell density at plateau phase was approximately 20%-30% of loaded cells.…”
Section: Discussionsupporting
confidence: 70%
“…Some researchers have reported that increasing the amount of gelatin in the scaffold can induce the binding and adhesion of the cells to the surface . Chitosan is a cationic polysaccharide capable of interacting with the surface anions and connecting the cell to the surface . Several studies have shown that Cs effective being in cell adhesion, its effect is, however, weaker than gel .…”
Section: Discussionmentioning
confidence: 99%
“…45 Chitosan is a cationic polysaccharide capable of interacting with the surface anions and connecting the cell to the surface. 46 Several studies have shown that Cs effective being in cell adhesion, its effect is, however, weaker than gel. 6,8 Nano-Hydroxyapatite is a bioceramic compound that comprises the natural mineral component of the bone.…”
Section: Discussionmentioning
confidence: 99%
“…Cell‐Mate3D hydrogels embedded with iPSCs were formed as previously described [13], except that here a chemically defined hydration fluid composed of buffered dextran was used. Briefly, as cells suspended in hydration fluid were added to the dry blend of hyaluronic acid and Chitosan under high agitation (vortexing), a gel formed instantly through polyelectrolytic complexation between HA COO‐ and CT NH3+ .…”
Section: Resultsmentioning
confidence: 99%